The Dynamics of the Internalization of Islamic Ethics in the Development of Academic Ethics Among Students at Al-Amien Prenduan University - Hendri Komara; Muhammad Nurul Yaqin (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2026)
The development of Artificial Intelligence in the field of education has facilitated the learning process, but it also poses serious challenges to academic ethics, such as an increased risk of plagiarism, technological dependence, and a weakening of intellectual responsibility. Ma’had Putra Universitas Al-Amien Prenduan, as a pesantren-based institution, plays a crucial role in instilling Islamic moral values to uphold the academic integrity of its students. This study focuses on two main aspects: (1) the internalization of Islamic moral values in shaping the academic ethics of students in the era of Artificial Intelligence, and (2) the transformation of Islamic moral education models in response to these technological developments. The research method employed is a descriptive qualitative approach using a case study design. Data collection techniques include observation, interviews, and documentation. Data analysis techniques involve data reduction, data presentation, and drawing conclusions. The research findings indicate that the internalization of Islamic moral values is carried out systematically and continuously through the strengthening of faith, the cultivation of religious practices, setting a good example, educational regulations, and supervision that are integrated into daily life at the boarding school. Values such as honesty (sidq), responsibility (mas’uliyyah), trustworthiness, piety, discipline (intizam), and humility (tawadhu’) have proven to play a crucial role in shaping the academic ethics of boarding school students, particularly in the wise and responsible use of Artificial Intelligence. Meanwhile, the transformation of Islamic moral education is adaptive and selective, with an emphasis on strengthening digital ethics, verifying understanding, and controlling the use of technology without eliminating the role of exemplary behavior and habit formation as the core of moral education.